SOCIO-PHILOSOPHICAL ANALYSIS OF THE FORMATION OF HISTORICAL CONSCIOUSNESS AND MEMORY IN YOUTH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
the article discusses the role of the concepts of historical consciousness and historical memory in the spiritual life of society and the formation of the national social memory created through it. Also, the social factors that are the main impetus for the formation of historical consciousness and historical memory, the writing of school history textbooks, their current situation, and the current state of social memory formed on this basis are described. At the same time, the teaching of national history in the general secondary education system of the post-Soviet countries, the attitudes of some countries to the study of the national history of other countries have been analyzed from the point of view of scientific objectivity.